디젤 엔진 0D 해석을 위한 CMC 모델 응용 - 권재성(Jaesung Kwon); 양정현(Jeonghyeon Yang); 김범수(Beomsoo Kim) (한국연소학회지, 2021)
A numerical analysis of the diesel engine performance and pollutant emissions was conducted by 0D simulation based on the CMC combustion model for turbulent diffusion flames. For the combustion analysis, the CMC model, the skeletal mechanism for n-heptane and the NOx mechanism included in GRI 3.0 were used. The evaporation process of fuel was simulated using the multizone spray model, and the density weighted PDF for the mixture fraction was calculated in real time based on the momentum conservation principle with the empirical models for spray tip velocity. The analysis was conducted by applying a multiple flame structure to the operating conditions of the multi-stage fuel injection method, and the predicted results well matched to the experimental data for the pressure variations. It also shows good qualitative and quantitative results for NOx. KCI Citation Count: 0